Socialization and Training of Value-added Tax (PPN) in Kerinjing Village, Ogan Ilir Regency - Ermadiani Ermadiani; Rina Tjandrakirana; Rochmawati Daud; Anton Indra Budiman (Faculty of Economics, Universitas Sriwijaya, 2022)
Kerinjing Village is one of 241 villages in Ogan Ilir Regency and one of 19 villages in Tanjung Raja District, which is 7 Km to the West from the District Capital and 13 Km to the East from the Regency Capital and has an area of ± 3 , 00 Km2. Kerinjing Village is divided into 2 hamlets led by each Hamlet Head. VAT is a tax imposed on any added value of goods or services in circulation from producers to consumers. VAT is a tax imposed on any added value of goods or services in circulation from producers to consumers. The training given to training participants uses the pedagogical learning method. This method provides training to participants where participants are considered as adults. The speaker provides training with a monologue then continues with a two-way dialogue between the resource person and the participants. Community service activities are carried out in Kerinjing Village and are carried out within 2 days. This service plan was carried out for 1 month. In this training, participants were also given examples of recording and calculating VAT. So far, they don't really understand and know about how to make correct financial records in accounting. Participants can try to make financial records according to the income they receive from their business and try to calculate the amount of tax to be paid and make tax reports. The service team provides direct guidance and assistance in making financial records, calculating the amount of tax to be paid based on the income received and making tax reports.